Polycrystalline alumina fiber and preparation method thereof
By using specific raw materials and processes to prepare polycrystalline alumina fibers and forming a modified film on their surface, the problem of electrostatic accumulation of alumina fibers during processing is solved, and the fibers are achieved with good antistatic effect and durability.
Patent Information
- Application Number
- CN202411775846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Alumina fibers are prone to static electricity during processing, resulting in increased processing difficulty and safety hazards, and existing antistatic agents are difficult to take effect for a long time.
Polycrystalline alumina fibers are prepared by mixing, stirring, concentration and dry spinning, and surface-modified films are formed by high-temperature firing and heat treatment to form surface-modified films to reduce the friction coefficient and surface resistance of the fibers.
The prepared alumina fibers have uniform components and good density, and have good anti-static effects. The surface modified layer is long-lasting and not easily affected by water washing and friction, which significantly reduces the static hazard and facilitates subsequent processing.
Smart Images

Figure BDA0005171420120000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular, relates to a polycrystalline alumina fiber and a preparation method thereof. Background Art
[0002] Polycrystalline alumina fiber is a new type of high-performance inorganic ceramic fiber. Its main component is Al 2O3, and it can also contain some other trace components, such as silicon dioxide, rare earth metals, etc. Alumina fiber includes three forms: long fiber, short fiber, and whisker. Alumina fiber has good high temperature resistance, corrosion resistance, high temperature oxidation resistance, low thermal conductivity, high strength and other advantages. It has great development potential and commercial value in the fields of military industry, aerospace, chemical industry, etc.
[0003] Alumina fiber is an excellent insulating material, but this also causes alumina fiber to easily generate static electricity due to friction during processing. Since the alumina fiber itself has a high electrical resistance and low water absorption, the static electricity formed is not easy to eliminate, so static electricity is easily accumulated. The accumulated static electricity will greatly increase the difficulty of processing alumina fiber and there are safety hazards. In the prior art, antistatic agents are often coated on the surface of alumina fibers and twisted to eliminate static electricity, but most of the antistatic agents coated on the surface are difficult to be effective for a long time. Based on this, the present invention provides a polycrystalline alumina fiber and a preparation method thereof, which are used to solve the problems existing in the above-mentioned background technology. Summary of the invention
[0004] The object of the present invention is to provide a polycrystalline alumina fiber and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 80-120 parts of aluminum powder, 0.8-1.2 parts of cerium nitrate hexahydrate, 0.4-0.6 parts of lanthanum nitrate hexahydrate, 80-100 parts of glacial acetic acid, 18-30 parts of silica sol, 8-12 parts of polyvinyl alcohol, and 0.4-0.8 parts of a wetting agent;
[0007] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0008] The first step is to weigh the raw materials according to the mass fractions: 80-120 parts of aluminum powder, 0.8-1.2 parts of cerium nitrate hexahydrate, 0.4-0.6 parts of lanthanum nitrate hexahydrate, 80-100 parts of glacial acetic acid, 18-30 parts of silica sol, 8-12 parts of polyvinyl alcohol, and 0.4-0.8 parts of a wetting agent;
[0009] Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed and nitric acid is added dropwise thereto to dissolve, and then glacial acetic acid is added to the solution, and the mixture is stirred to obtain a prefabricated sol;
[0010] The third step is to mix the prefabricated sol, silica sol and polyvinyl alcohol, stir them evenly, concentrate them and obtain prefabricated fibers through dry spinning;
[0011] The fourth step is to prepare a pretreatment liquid with the impregnating agent and anhydrous ethanol, and then pre-sinter the prefabricated fiber and then sinter it at high temperature to form it. Finally, the sintered fiber is added to the pretreatment liquid for heat treatment to obtain a polycrystalline alumina fiber.
[0012] Furthermore, the nitric acid used is a nitric acid aqueous solution with a mass fraction of 3-6%.
[0013] Furthermore, the mass fraction of the silica sol used is 10%.
[0014] Furthermore, in the second step, after nitric acid is added dropwise and dissolved, the pH value of the solution is 2-3.
[0015] Furthermore, the viscosity of the concentrated preformed sol in the third step is 1600-1700 mPa·s.
[0016] Furthermore, the mass ratio of the wetting agent and anhydrous ethanol used in the fourth step is 1:250.
[0017] Furthermore, in the fourth step, the pre-sintering condition is to sinter at a temperature of 160-200° C. for 1.5-2 h, and the high temperature sintering condition is to sinter at a temperature of 1000-1200° C. for 5-6 h.
[0018] Furthermore, the heat treatment in the fourth step is carried out at a temperature of 40-60° C. for 2-3 hours.
[0019] Furthermore, the infiltrant is prepared by the following steps.
[0020] Step 1, 3-amino-4-bromobenzenesulfonic acid, lauroyl chloride, triethylamine and toluene are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the mixture is reacted at 60° C. for 4-6 hours. After the reaction is completed, deionized water is added to the three-necked flask for washing, and the mixture is extracted with dichloromethane. The organic layer is then separated with a separatory funnel, and the organic layer is rotary evaporated to obtain intermediate 1;
[0021] Step 2, the intermediate 1, dodecane bromide and ethanol are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Then, sodium hydroxide is added to the three-necked flask, and the mixture is reacted at 40-50° C. for 24 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the remaining solid is subjected to silica gel column chromatography to obtain the intermediate 2;
[0022] Step 3, N,N-dimethylglycyl chloride, hydroxymethyltriethoxysilane, triethylamine, and N,N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at a temperature of 90-110° C. for 4-6 hours. After the reaction was completed, a saturated sodium bicarbonate solution was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 3;
[0023] Step 4: Mix intermediate 2, intermediate 3 and acetonitrile in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at a temperature of 50-60°C for 24 hours. After the reaction is completed, remove the solvent by rotary evaporation, and obtain the wetting agent by silica gel column chromatography on the remaining solid.
[0024] Furthermore, the dosage ratio of 3-amino-4-bromobenzenesulfonic acid, lauroyl chloride, triethylamine and toluene used in step 1 is 0.1-0.11 mol: 0.1 mol: 0.12-0.14 mol: 80-100 mL.
[0025] Furthermore, the usage ratio of intermediate 1, dodecane bromide, ethanol and sodium hydroxide used in step 2 is 0.08 mol: 0.08-0.1 mol: 40-60 mL: 5 g.
[0026] Furthermore, the amount ratio of N,N-dimethylglycyl chloride, hydroxymethyltriethoxysilane, triethylamine and N,N-dimethylformamide used in step 3 is 0.1 mol: 0.1 mol: 0.12-0.14 mol: 60-80 mL.
[0027] Furthermore, the usage ratio of intermediate 2, intermediate 3 and acetonitrile used in step 4 is 0.05 mol:0.05 mol:40-60 mL.
[0028] Beneficial effects of the present invention:
[0029] 1) The present invention uses aluminum powder, cerium nitrate hexahydrate, lanthanum nitrate hexahydrate, glacial acetic acid, silica sol, polyvinyl alcohol, and a wetting agent as raw materials to prepare a polycrystalline alumina fiber. The present invention prepares a polycrystalline alumina fiber by first mixing aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate and dissolving them with nitric acid, then adding glacial acetic acid to prepare a prefabricated sol, then mixing the prefabricated sol, silica sol and polyvinyl alcohol together, stirring and concentrating to prepare a prefabricated fiber, and finally sintering the prefabricated fiber into a shape and then surface-modifying the sintered fiber with a wetting agent to obtain a polycrystalline alumina fiber. The alumina fiber prepared by the preparation method of the present invention has uniform components and good fiber density, and the wetting agent on the surface of the prepared alumina fiber can also reduce the friction coefficient and surface resistance of the alumina fiber, and is not easy to cause static electricity hazards.
[0030] 2) The present invention uses 3-amino-4-bromobenzenesulfonic acid and lauroyl chloride as raw materials, and an amidation reaction is carried out between the amino group of 3-amino-4-bromobenzenesulfonic acid and the acyl chloride group of lauroyl chloride under the condition of triethylamine as an acid binding agent to obtain intermediate 1, and then uses intermediate 1 as a raw material, and utilizes the imino group of intermediate 1 and the bromine atom of bromododecane to undergo a nucleophilic substitution reaction under an alkaline environment to obtain intermediate 2. At the same time, the present invention uses N,N-dimethylglycyl chloride and hydroxymethyltriethoxysilane as raw materials, and an esterification reaction is carried out between the acyl chloride group of N,N-dimethylglycyl chloride and the hydroxyl group of hydroxymethyltriethoxysilane to obtain intermediate 3. Finally, intermediate 2 and intermediate 3 are used as raw materials to make the intermediate 2 The bromine atom and the intermediate 3 react to form a quaternary ammonium salt to obtain the wetting agent. The wetting agent prepared by the present invention has a siloxane structure and can react with the hydroxyl groups on the surface of the polycrystalline alumina fiber to form a directional thin film on the surface of the polycrystalline alumina fiber. The thin film has a hydrophilic sulfonic acid group structure and a quaternary ammonium salt structure and a lipophilic long-chain alkyl structure and an ester group and an amide group structure. It can not only form a conductive path on the surface of the polycrystalline alumina fiber to reduce the surface resistance of the alumina fiber, but also play a lubricating role to reduce the friction coefficient of the polycrystalline alumina fiber. In addition, the thin film is bonded by chemical bonds, so it has good durability, is not easily affected by factors such as water washing and friction, and can be effective for a long time.
[0031] 3) The alumina fiber prepared by the preparation method of the present invention has uniform components and good density, has a good and lasting antistatic effect, is not easy to cause static electricity hazards, is convenient for subsequent processing, and can be widely used in the field of electronics industry. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] A wetting agent is prepared by the following steps:
[0035] Step 1, 0.1 mol 3-amino-4-bromobenzenesulfonic acid, 0.1 mol lauroyl chloride, 0.12 mol triethylamine, and 80 mL toluene were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 60° C. for 4 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0036] Step 2, 0.08 mol intermediate 1, 0.08 mol bromododecane, and 40 mL ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 5 g of sodium hydroxide was added to the three-necked flask, and the mixture was reacted at 40° C. for 24 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was subjected to silica gel column chromatography to obtain intermediate 2;
[0037] Step 3, 0.1 mol N, N-dimethylglycyl chloride, 0.1 mol hydroxymethyltriethoxysilane, 0.12 mol triethylamine, and 60 mL N, N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 90° C. for 4 h. After the reaction was completed, a saturated sodium bicarbonate solution was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 3;
[0038] Step 4: Mix 0.05 mol intermediate 2, 0.05 mol intermediate 3, and 40 mL acetonitrile in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at 50°C for 24 hours. After the reaction is completed, remove the solvent by rotary evaporation, and obtain the wetting agent by silica gel column chromatography on the remaining solid.
[0039] Example 2
[0040] A wetting agent is prepared by the following steps:
[0041] Step 1, 0.105 mol 3-amino-4-bromobenzenesulfonic acid, 0.1 mol lauroyl chloride, 0.13 mol triethylamine, and 90 mL toluene were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 60° C. for 5 hours. After the reaction was completed, deionized water was added to the three-necked flask for washing, and extracted with dichloromethane, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0042] Step 2, 0.08 mol intermediate 1, 0.09 mol bromododecane, and 50 mL ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 5 g of sodium hydroxide was added to the three-necked flask, and the mixture was reacted at 45° C. for 24 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was subjected to silica gel column chromatography to obtain intermediate 2;
[0043] Step 3, 0.1 mol N, N-dimethylglycyl chloride, 0.1 mol hydroxymethyltriethoxysilane, 0.13 mol triethylamine, 70 mL N, N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 100 ° C for 5 hours. After the reaction was completed, a saturated sodium bicarbonate solution was added to the three-necked flask for washing, and extracted with dichloromethane, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 3;
[0044] Step 4: Mix 0.05 mol intermediate 2, 0.05 mol intermediate 3, and 50 mL acetonitrile in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at 55°C for 24 hours. After the reaction is completed, remove the solvent by rotary evaporation, and obtain the wetting agent by silica gel column chromatography on the remaining solid.
[0045] Example 3
[0046] A wetting agent is prepared by the following steps:
[0047] Step 1, 0.11 mol 3-amino-4-bromobenzenesulfonic acid, 0.1 mol lauroyl chloride, 0.14 mol triethylamine, and 100 mL toluene were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 60° C. for 6 hours. After the reaction was completed, deionized water was added to the three-necked flask for washing, and extracted with dichloromethane, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0048] Step 2, 0.08 mol intermediate 1, 0.1 mol bromododecane, and 60 mL ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, and magnetic stirring was turned on. Then, 5 g of sodium hydroxide was added to the three-necked flask, and the mixture was reacted at 50° C. for 24 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the remaining solid was subjected to silica gel column chromatography to obtain intermediate 2;
[0049] Step 3, 0.1 mol N, N-dimethylglycyl chloride, 0.1 mol hydroxymethyltriethoxysilane, 0.14 mol triethylamine, and 80 mL N, N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 110° C. for 6 h. After the reaction was completed, a saturated sodium bicarbonate solution was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 3;
[0050] Step 4: Mix 0.05 mol intermediate 2, 0.05 mol intermediate 3, and 60 mL acetonitrile in a three-necked flask, install a condenser and a thermometer, turn on magnetic stirring, and react at 60°C for 24 hours. After the reaction is completed, remove the solvent by rotary evaporation, and obtain the wetting agent by silica gel column chromatography on the remaining solid.
[0051] Example 4
[0052] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 80 parts of aluminum powder, 0.8 parts of cerium nitrate hexahydrate, 0.4 parts of lanthanum nitrate hexahydrate, 80 parts of glacial acetic acid, 18 parts of silica sol, 8 parts of polyvinyl alcohol, and 0.4 parts of the wetting agent obtained in Example 1;
[0053] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0054] The first step is to weigh the raw materials by mass: 80 parts of aluminum powder, 0.8 parts of cerium nitrate hexahydrate, 0.4 parts of lanthanum nitrate hexahydrate, 80 parts of glacial acetic acid, 18 parts of silica sol, 8 parts of polyvinyl alcohol, and 0.4 parts of the wetting agent obtained in Example 1;
[0055] Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed, and a 3% by mass nitric acid aqueous solution is dripped into the mixture until the mixture is dissolved and the pH value of the solution reaches 2, and then glacial acetic acid is added to the solution, and the mixture is stirred and mixed to obtain a prefabricated sol;
[0056] The third step is to mix the prefabricated sol, 10% silica sol and polyvinyl alcohol, stir them evenly and concentrate them to a viscosity of 1600 mPa·s, and obtain prefabricated fibers by dry spinning;
[0057] The fourth step is to prepare a pretreatment liquid with the impregnating agent obtained in Example 1 and anhydrous ethanol in a mass ratio of 1:250, and then pre-sinter the prefabricated fiber at a temperature of 160°C for 1.5 hours and then sinter it at a temperature of 1000°C for 5 hours to form it. Finally, add the sintered fiber to the pretreatment liquid and heat treat it at a temperature of 40°C for 2 hours to obtain a polycrystalline alumina fiber.
[0058] Example 5
[0059] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 100 parts of aluminum powder, 1 part of cerium nitrate hexahydrate, 0.5 parts of lanthanum nitrate hexahydrate, 90 parts of glacial acetic acid, 24 parts of silica sol, 10 parts of polyvinyl alcohol, and 0.6 parts of the wetting agent obtained in Example 2;
[0060] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0061] The first step is to weigh the raw materials by mass: 100 parts of aluminum powder, 1 part of cerium nitrate hexahydrate, 0.5 parts of lanthanum nitrate hexahydrate, 90 parts of glacial acetic acid, 24 parts of silica sol, 10 parts of polyvinyl alcohol, and 0.6 parts of the wetting agent obtained in Example 2;
[0062] Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed, and a 4% by mass nitric acid aqueous solution is added dropwise thereto until the mixture is dissolved and the pH value of the solution reaches 2.5, and then glacial acetic acid is added to the solution, and the mixture is stirred and mixed to obtain a prefabricated sol;
[0063] The third step is to mix the prefabricated sol, 10% silica sol and polyvinyl alcohol, stir them evenly and concentrate them to a viscosity of 1650 mPa·s, and obtain prefabricated fibers by dry spinning;
[0064] The fourth step is to prepare a pretreatment liquid with the impregnating agent obtained in Example 2 and anhydrous ethanol in a mass ratio of 1:250, and then pre-sinter the prefabricated fiber at a temperature of 180°C for 1.75 hours and then sinter it at a temperature of 1100°C for 5.5 hours to form it. Finally, add the sintered fiber to the pretreatment liquid and heat treat it at a temperature of 50°C for 2.5 hours to obtain a polycrystalline alumina fiber.
[0065] Example 6
[0066] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 120 parts of aluminum powder, 1.2 parts of cerium nitrate hexahydrate, 0.6 parts of lanthanum nitrate hexahydrate, 100 parts of glacial acetic acid, 30 parts of silica sol, 12 parts of polyvinyl alcohol, and 0.8 parts of the wetting agent obtained in Example 3;
[0067] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0068] The first step is to weigh the raw materials by mass: 120 parts of aluminum powder, 1.2 parts of cerium nitrate hexahydrate, 0.6 parts of lanthanum nitrate hexahydrate, 100 parts of glacial acetic acid, 30 parts of silica sol, 12 parts of polyvinyl alcohol, and 0.8 parts of the wetting agent obtained in Example 3;
[0069] Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed, and a 6% by mass nitric acid aqueous solution is dripped into the mixture until the mixture is dissolved and the pH value of the solution reaches 3, and then glacial acetic acid is added to the solution, and the mixture is stirred to obtain a prefabricated sol;
[0070] The third step is to mix the prefabricated sol, 10% silica sol and polyvinyl alcohol, stir them evenly and concentrate them to a viscosity of 1700 mPa·s, and obtain prefabricated fibers by dry spinning;
[0071] The fourth step is to prepare a pretreatment liquid with anhydrous ethanol in a mass ratio of 1:250. The prefabricated fiber is first pre-fired at 200°C for 2 hours and then fired at 1200°C for 6 hours to form a fiber. Finally, the fired fiber is added to the pretreatment liquid and heat-treated at 60°C for 3 hours to obtain a polycrystalline alumina fiber.
[0072] Comparative Example 1
[0073] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 120 parts of aluminum powder, 1.2 parts of cerium nitrate hexahydrate, 0.6 parts of lanthanum nitrate hexahydrate, 100 parts of glacial acetic acid, 30 parts of silica sol, and 12 parts of polyvinyl alcohol;
[0074] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0075] The first step is to weigh the raw materials according to the mass fractions: 120 parts of aluminum powder, 1.2 parts of cerium nitrate hexahydrate, 0.6 parts of lanthanum nitrate hexahydrate, 100 parts of glacial acetic acid, 30 parts of silica sol, and 12 parts of polyvinyl alcohol;
[0076] Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed, and a 6% by mass nitric acid aqueous solution is dripped into the mixture until the mixture is dissolved and the pH value of the solution reaches 3, and then glacial acetic acid is added to the solution, and the mixture is stirred to obtain a prefabricated sol;
[0077] The third step is to mix the prefabricated sol, 10% silica sol and polyvinyl alcohol, stir them evenly and concentrate them to a viscosity of 1700 mPa·s, and obtain prefabricated fibers by dry spinning;
[0078] The fourth step is to pre-sinter the prefabricated fiber at 200°C for 2 hours and then sinter it at 1200°C for 6 hours to form it. Finally, the sintered fiber is added to anhydrous ethanol and heat-treated at 60°C for 3 hours to obtain a polycrystalline alumina fiber.
[0079] Comparative Example 2
[0080] A polycrystalline alumina fiber comprises the following raw materials in parts by weight: 120 parts of aluminum powder, 100 parts of glacial acetic acid, 30 parts of silica sol, and 12 parts of polyvinyl alcohol;
[0081] A method for preparing polycrystalline alumina fiber comprises the following steps:
[0082] The first step is to weigh the raw materials according to their mass fractions: 120 parts of aluminum powder, 100 parts of glacial acetic acid, 30 parts of silica sol, and 12 parts of polyvinyl alcohol;
[0083] Step 2: dripping 6% nitric acid aqueous solution into the aluminum powder until the aluminum powder is dissolved and the pH value of the solution reaches 3, then adding glacial acetic acid to the solution, stirring and mixing to obtain a prefabricated sol;
[0084] The third step is to mix the prefabricated sol, 10% silica sol and polyvinyl alcohol, stir them evenly and concentrate them to a viscosity of 1700 mPa·s, and obtain prefabricated fibers by dry spinning;
[0085] The fourth step is to pre-sinter the prefabricated fiber at 200°C for 2 hours and then sinter it at 1200°C for 6 hours to form it. Finally, the sintered fiber is added to anhydrous ethanol and heat-treated at 60°C for 3 hours to obtain a polycrystalline alumina fiber.
[0086] Comparative Example 3
[0087] This comparative example is the high-purity alumina fiber sold by Ningbo Jiweinano New Material Technology Co., Ltd. and the antistatic finishing agent sold by Guangzhou Junyu New Materials Co., Ltd.
[0088] A pretreatment liquid is prepared by mixing a commercial antistatic finishing agent with anhydrous ethanol in a mass ratio of 1:250, and then commercial alumina fibers are added into the pretreatment liquid and soaked to obtain commercial antistatic agent-modified alumina fibers.
[0089] The surface resistance of the polycrystalline alumina fibers in Examples 4-6 and Comparative Examples 1-2 and the commercially available antistatic agent-modified alumina fibers in Comparative Example 3 was tested using a point-to-point resistance tester sold by Dongguan Bolide Instrument Equipment Co., Ltd. After washing 5 times, the test was repeated. The test results are shown in Table 1:
[0090] Table 1
[0091]
[0092] It can be seen from Table 1 that the surface resistance of the polycrystalline alumina in Examples 4-6 of the present invention is much lower than that of the commercially available antistatic agent modified alumina fiber, and the surface resistance is almost unaffected after washing, indicating that the polycrystalline alumina fiber of the present invention has good antistatic effect and lasts for a long time, and is therefore easy to process; Comparative Examples 1-2 respectively carried out control experiments on the cerium nitrate hexahydrate, lanthanum nitrate hexahydrate, and wetting agent used in the present invention, and the final results showed that it is the wetting agent of the present invention that plays a role in reducing the surface resistance of the alumina fiber. In summary, the polycrystalline alumina fiber of the present invention has good antistatic effect and can be widely used in the electronics industry.
[0093] The above is a detailed introduction to a polycrystalline alumina fiber and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combination method. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The reason why these combinations are not exhaustively described in this specification is only for the purpose of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A polycrystalline alumina fiber, characterized in that: The raw materials include the following parts by weight: 80-120 parts of aluminum powder, 0.8-1.2 parts of cerium nitrate hexahydrate, 0.4-0.6 parts of lanthanum nitrate hexahydrate, 80-100 parts of glacial acetic acid, 18-30 parts of silica sol, 8-12 parts of polyvinyl alcohol, and 0.4-0.8 parts of a wetting agent; Wherein, the infiltrant is prepared by the following steps: Step 1, 3-amino-4-bromobenzenesulfonic acid, lauroyl chloride, triethylamine and toluene are mixed in a container, stirred evenly, and reacted at 60° C. for 4-6 hours to obtain intermediate 1; Step 2, mixing intermediate 1, dodecane bromide and ethanol in a container, stirring evenly, adding sodium hydroxide to the container, and reacting at 40-50° C. for 24 hours to obtain intermediate 2; Step 3, N,N-dimethylglycyl chloride, hydroxymethyltriethoxysilane, triethylamine and N,N-dimethylformamide are mixed in a container, stirred evenly, and reacted at a temperature of 90-110° C. for 4-6 hours to obtain intermediate 3; Step 4: Mix the intermediate 2, the intermediate 3 and acetonitrile in a container, stir evenly, and react at a temperature of 50-60° C. for 24 hours to obtain the wetting agent.
2. The polycrystalline alumina fiber according to claim 1, characterized in that: The amount ratio of 3-amino-4-bromobenzenesulfonic acid, lauroyl chloride, triethylamine and toluene used in step 1 is 0.1-0.11 mol: 0.1 mol: 0.12-0.14 mol: 80-100 mL.
3. The polycrystalline alumina fiber according to claim 1, characterized in that: The amount ratio of intermediate 1, dodecane bromide, ethanol and sodium hydroxide used in step 2 is 0.08 mol: 0.08-0.1 mol: 40-60 mL: 5 g.
4. The polycrystalline alumina fiber according to claim 1, characterized in that: The amount ratio of N,N-dimethylglycyl chloride, hydroxymethyltriethoxysilane, triethylamine and N,N-dimethylformamide used in step 3 is 0.1 mol: 0.1 mol: 0.12-0.14 mol: 60-80 mL.
5. The polycrystalline alumina fiber according to claim 1, characterized in that: The amount ratio of intermediate 2, intermediate 3 and acetonitrile used in step 4 is 0.05 mol: 0.05 mol: 40-60 mL.
6. A method for preparing polycrystalline alumina fiber according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: The first step is to weigh the raw materials according to the mass fractions: 80-120 parts of aluminum powder, 0.8-1.2 parts of cerium nitrate hexahydrate, 0.4-0.6 parts of lanthanum nitrate hexahydrate, 80-100 parts of glacial acetic acid, 18-30 parts of silica sol, 8-12 parts of polyvinyl alcohol, and 0.4-0.8 parts of a wetting agent; Step 2: Aluminum powder, cerium nitrate hexahydrate, and lanthanum nitrate hexahydrate are mixed and nitric acid is added dropwise thereto to dissolve, and then glacial acetic acid is added to the solution, and the mixture is stirred to obtain a prefabricated sol; The third step is to mix the prefabricated sol, silica sol and polyvinyl alcohol, stir them evenly, concentrate them and obtain prefabricated fibers through dry spinning; The fourth step is to prepare a pretreatment liquid with the impregnating agent and anhydrous ethanol, and then pre-sinter the prefabricated fiber and then sinter it at high temperature to form it. Finally, the sintered fiber is added to the pretreatment liquid for heat treatment to obtain a polycrystalline alumina fiber.
7. The method for preparing polycrystalline alumina fiber according to claim 6, characterized in that: The nitric acid used is a nitric acid aqueous solution with a mass fraction of 3-6%, and the mass fraction of the silica sol used is 10%.
8. The method for preparing polycrystalline alumina fiber according to claim 6, characterized in that: In the second step, after nitric acid is added dropwise to dissolve, the pH value of the solution is 2-3.
9. The method for preparing polycrystalline alumina fiber according to claim 6, characterized in that: The viscosity of the concentrated preformed sol in the third step is 1600-1700 mPa·s.
10. The method for preparing polycrystalline alumina fiber according to claim 6, characterized in that: The mass ratio of the wetting agent and anhydrous ethanol used in the fourth step is 1:
250. The pre-sintering conditions in the fourth step are firing at a temperature of 160-200°C for 1.5-2h, the high-temperature sintering conditions are firing at a temperature of 1000-1200°C for 5-6h, and the heat treatment conditions in the fourth step are treating at a temperature of 40-60°C for 2-3h.